2006
DOI: 10.1073/pnas.0604419103
|View full text |Cite
|
Sign up to set email alerts
|

Variation at the rat Crhr1 locus and sensitivity to relapse into alcohol seeking induced by environmental stress

Abstract: Alcoholism is a chronic relapsing disorder with substantial heritability. Uncovering gene-environment interactions underlying this disease process can aid identification of novel treatment targets. Here, we found a lowered threshold for stress-induced reinstatement of alcohol seeking in Marchigian-Sardinian Preferring (msP) rats genetically selected for high alcohol preference. In situ hybridization for a panel of 20 stress-related genes in 16 brain regions was used to screen for differential gene expression t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
281
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(313 citation statements)
references
References 32 publications
26
281
1
5
Order By: Relevance
“…2 [6,23]. As predicted from the allostatic concept of addiction (Box 1) we found upregulated CRH activity in the central amygdala of postdependent animals during acute withdrawal and many weeks thereafter, contributing to increased ethanol intake, anxiety, and ethanol-seeking behavior, all of which can be alleviated by blockade of CRH 1 receptors [6,[23][24][25][26]. In fact, the excessive ethanol consumption appears to be a means to downregulate amygdala CRH 1 receptors [27].…”
Section: Introductionsupporting
confidence: 51%
“…2 [6,23]. As predicted from the allostatic concept of addiction (Box 1) we found upregulated CRH activity in the central amygdala of postdependent animals during acute withdrawal and many weeks thereafter, contributing to increased ethanol intake, anxiety, and ethanol-seeking behavior, all of which can be alleviated by blockade of CRH 1 receptors [6,[23][24][25][26]. In fact, the excessive ethanol consumption appears to be a means to downregulate amygdala CRH 1 receptors [27].…”
Section: Introductionsupporting
confidence: 51%
“…A 15-min electric (1.0 mA current intensity) footshock stress was delivered via the grid floor of the chamber under a variable-interval 40-s schedule (interval range: 10-70 s). We choose 1.0 mA because in a previous study (Hansson et al 2006), we showed that in Wistar rats, the maximum level of responding is obtained at this current intensity. After termination of footshock, the levers were extended into the chambers, and responses were recorded for 30 min.…”
Section: Footshock Stress-induced Reinstatementmentioning
confidence: 99%
“…For various endocrine-independent effects of chronic EtOH, more profound effects of CRF 1 receptor manipulations have been described in postdependent animals and in animals that were selectively bred for elevated EtOH preference (54,58,59). CRF 1 receptor antagonists can reduce levels of intake of postdependent animals to the levels observed in nondependent ones (54,58,59).…”
Section: Discussionmentioning
confidence: 99%
“…Given the comorbidity of drug addiction with affective disorders, CRF systems have been suggested as potential common targets for their treatment (50,53). Regarding alcoholism, human and rodent data support a genetically determined relationship between central CRF function and EtOH consumption (54)(55)(56)(57). EtOH-induced longterm neuroadaptations responsible for increased EtOH intake and stress-evoked relapse-like behavior in EtOH-dependent animals withdrawn from EtOH have also been linked to CRF function (54,58,59), and repeated EtOH exposure sensitizes the response to the activating effects of a central CRF administration (40).…”
Section: Deletion Of Ucn 1 Does Not Prevent Psychomotor Sensitizationmentioning
confidence: 99%